Research on the optimization of proportions for synchronous grouting material in composite muck during shield tunneling - Zhang, Jian; Zhu, Cheng; Kuang, Mengxiang; Xu, Tao; Wang, Xiaohu; Feng, Tugen; Xu, Jingmin (Journal of cleaner production, 2024)
To tackle the challenge of onsite resource reuse of composite muck, which relies on a shield tunneling section in the case of Nanjing Metro Line 7, this paper examines the effects of component substitution and varying proportions of factors on slurry properties through laboratory tests and multiobjective modeling. From a practical application perspective, the potential of using composite muck as a synchronous grouting material for shield tunneling was explored. In reference to the common mixed strata encountered in shield tunneling construction in the Nanjing area, a general slurry mixing ratio suitable for various mixed strata conditions was derived. The research results indicate the following optimized mixing ratios for the composite muck slurry: a water-to-binder (cement + fly ash) ratio of 0.76, a cement-to-fly ash ratio of 0.53, a binder-to-soil (silty clay + silty fine sand + river sand) ratio of 0.67, a clay (i.e., silty clay)-to-sand (i.e., silty fine sand + river sand) ratio of 0.4, and a substitution ratio (i.e., silty fine sand/silty fine sand + river sand) of 0.2. This slurry is feasible for practical applications and can reduce construction costs by 38.13%. The obtained general mixing ratio for the composite muck slurry, suitable for various mixed stratigraphic conditions, essentially meets onsite construction requirements (the bleeding rate is controlled within a low range of 1.1–3.1%, and the maximum compressive strength reaches up to 6.76 MPa at 28 days), with reasonable costs. It streamlines construction by eliminating the need for onsite screening of muck, allowing for the direct onsite reuse of composite muck in shield tunneling. •The feasibility of using composite muck as a synchronous grouting material was systematically investigated.•The optimized mixing ratio for the slurry performance was obtained by the goal programming method.•The properties of stone bodies in the slurry were characterized from a microscopic perspective.•A general slurry mixing ratio suitable for various mixed stratigraphic conditions was established.